Microsoft System Center Virtual Machine Manager 2012 cookbook : over 60 recipes for the administration and management of Microsoft System Center Virtual Machine Manager 2012 SP1 /: over 60 recipes for the administration and management of Microsoft System Center Virtual Machine Manager 2012 SP1. (2013) - Unknown
No abstract available